Legislação e programa de estudo do Ensino Religioso da Alemanha - Batista, Débora Carvalho (2022)
This thesis focuses on the current German confessional and nondenominational Religious Education, aiming to understand it in its national legal structure of each Federal State. And to discuss the curricula of four German States: Thuringia and Saxony (located in areas of former East Germany), Lower Saxony and Bavaria (located in areas of former West Germany). Further objectives of this research are: to understand the religious situation in Germany as a context for Religious Education; to study the Religious Education in the Federal Republic of Germany (from 1947 onwards); to present the legal regulation of Religious Education in the States of the Federal Republic of Germany; to address the curricula of Christian, non-Christian and alternative Religious Education, to analyze to what extent non-Christian religions are addressed in German Religious Education curricula